Pemanfaatan Penggunaan Ice - breaking pada Website Baamboozle dalam Kegiatan Pembelajaran - Iin Andriyani; Meilani Feradona; Vianka Putri Rizaldi (Program Studi PGSD Kampus UPI di Serang, 2021)
Technological advancements are inescapable at this point. As we all know, in the technology era, we now have easy access to the internet. Before starting learning activities, an educator should establish a pleasant atmosphere for students, to advoid boredom, tedium, or fear. An educator can tackle this problem by implementing ice-breaking activities before the learning session. One of the technological conveniences that educators can use is the ice-breaking website on the internet, one of which is the Baamboozle website. As a result, the purpose of this article is finds out how to use ice-breaking on the Baamboozle website in learning activities. The author uses a qualitative method in conducting research on the usage of ice-breaking on the Baamboozle website in learning activities. The literature technique is used to obtain data in this article. The literature technique entails a set of procedures that include gathering library data, reading and taking notes, and organizing research resources. The results and discussion suggest that using ice-breaking activities on the Baamboozle website can assist educators in providing the best atmosphere for students to achieve their learning objectives.